TICS as a key factor in the academic and administrative management of the university - Espinoza Altamirano, Manuel Jorge (2018)
Now a days there are coincidences in recognizingthat in the context of universities the influence of the technologies in university management isgravitating, as well as the impact and challenge that has to face the new challenges of the academic and administrative management of the university . The researchstudywillconcentrateits perspective on the dimension of technologicaldevelopment, itis a phenomenon of rapid accumulation of information of knowledge. The new information technologies and telecommunicationsoffer an enormouspotential for transformingeducationalsystems and disseminatingtheir productive applications, whichisachievedthrough a systematicactivity of uses of the capacities of the mind, known as knowledge And researchthatmakesit crucial thatitsacademicimplementation and developmentrequest administrative management withorganizationalmodelsthatimplyquality in itsprocesses and resourcesinteractwith the intensive use of technology. The technologies allow the development of learningsystemsparallel to the formaleducation system wenow know, systemswiththeirowntitles and certifications, institutionalflexibility and adapted to the specificneeds of eachstudent. The role of the administrative administration in the implementation and development of technologies demandsreplacingitsorganizationalmodelsassuming an accreditedquality management, continuousimprovement and guaranteeing excellence and competitiveness.